Statistical evaluation of creation and liquidation of organizations in Russia: sectoral and regional aspects - Yu. S. Pinkovetskaya (Статистика и экономика)
The  urgency of a comprehensive  assessment  of the current patterns of establishment  and liquidation  of legal entities in Russia  is due to standing problems of the development  of the national  economy  and increasing the volume of production of goods and rendering of various services, including based on accelerated growth of import substitution. The purpose of the study: to assess the current  demography  of organizations  in Russia,  namely  the levels of fertility and  liquidation of organizations.  The  analytical  assessment is based on two aspects of organizational  demography:  sectoral and  regional. To  provide  a comparative  analysis  the  assessment  was  carried  out  according  to the data for 2017 and 2018.Materials and  methods.  In  the  course of the  study,  the  following indicators  were  considered  for  19  types  of  economic  activity  and 82 regions of our country  for 2017  and  2018  as the  share of new organizations  in the  total number  of functioning  organizations,  the share of liquidated  organizations,  as well as the existing ratio of the number of new and liquidated  organizations. Official information  of the Federal  State  Statistics  Service  on institutional  transformations in the economy and demography of organizations was used as initial data.  The  research  methodology  is based  on  the  consideration  of newly  created and  liquidated  organizations  formed by industry  and territorial characteristics. Modeling of values’ differentiation of specific weights of such organizations  in the total number  of the functioning organizations  was carried out with the use of functions of density of normal distribution.Results.  According to the results of the study,  the values  of specific weights of new and liquidated  organizations in their total number by industry  and  regions of the country were determined;  it was shown that the number of liquidated organizations in most regions and types of economic  activities for the period exceeded  the number  of newly created  organizations;  lists of regions and  industries  with  high and low values of the considered indicators were established.  The  study tested and confirmed the following two hypotheses: the presence of a significant differentiation  of the specific weights of created and liquidated  organizations  in the total number  of organizations  by types of economic activity; the presence of a significant differentiation  of the specific weights of created  and  liquidated  organizations  in the total number  of organizations  by region. Conclusion. The results are of theoretical importance in the conduct of research and training of students. Functions of density of normal distribution can be used at justification of plans and programs of development of economy of regions. The practical significance of the research results is associated with the possibility of their use in assessing the possibility of creating enterprises in specific industries and regions. The  units of regional  and  municipal  authorities  monitoring  the  business  climate can use the results of the work.  The  given methodological  approach and  obtained  analytical  estimates  are of interest  to financial  credit and leasing companies in the justification of their policies, taking into account various activities and regional characteristics.